ImageJS: plataforma Javascript para composição de um minieditor de imagens - Ribas, Lucian Rossoni (2017)
Currently, the major platforms developed for image editing are still predominantly targeted to desktop devices; however, the increase in computational capacity directed at resources for the Internet is slowly triggering the migration of these programs to the Web environment, this includes softwares developed for image manipulation, defining the scope of this project. Available in the format of a mini studio with JavaScript libraries and dependencies, this platform aims to incorporate in a Web page a small editor for manipulation of images, graphically grouping some tools that allow the user to apply basic manipulations to an image. The image can be selected as a file, by the local directories tree, or sent from an external remote address. Due to the intention of being a cross-browser library, it will be very useful for Web-based system developers, who will not need to implement modules related to basic image editions.